2021
DOI: 10.1093/ofid/ofab103
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Reverse-Transcriptase Inhibitor Resistance Mutations Predict Virological Failure in Human Immunodeficiency Virus-Positive Patients During Lamivudine Plus Dolutegravir Maintenance Therapy in Clinical Practice

Abstract: The TANGO trial demonstrated the efficacy of lamivudine plus dolutegravir in virologically suppressed patients without previous virological failures (VF). In this dataset from clinical practice investigating the impact of past NRTI resistance on this strategy, the combination of M184V/I plus at least one TAM significantly increased the risk of VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Characteristics of the 5 real-world cohorts that met all search criteria and were included in the meta-analysis are summarized in Table 1 and indicated by lead cohort publication. Of these cohorts, 2 used similar criteria to define VF [ 13 , 14 ]; 3 reported VF outcomes at all time points [ 13 , 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the 5 real-world cohorts that met all search criteria and were included in the meta-analysis are summarized in Table 1 and indicated by lead cohort publication. Of these cohorts, 2 used similar criteria to define VF [ 13 , 14 ]; 3 reported VF outcomes at all time points [ 13 , 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Key findings related to VF in RWE cohorts are summarized in Table 2 . One cohort observed that presence of M184V/I had no impact on virologic suppression with DTG + 3TC [ 19 ], and another found that presence of M184V/I did not predict VF [ 17 ] but did predict shorter time to VF (vs absence [ 16 ]); 3 cohorts found that evidence of M184V/I did not affect probability of VF for ≥1 year [ 13 , 14 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar case has been reported [ 18 ]. In line with these considerations, the TANGO trial [ 19 ] found the combination of M184V/I and at least one TAM and previous failure on an INSTI-based regimen to predict failure upon switching to lamivudine and dolutegravir, highlighting the importance of an optimal NRTI backbone for virologic success. Although the overall finding from the NADIA trial [ 15 ] was noninferiority between dolutegravir and ritonavir boosted darunavir (darunavir/r) in combination with either tenofovir or zidovudine as second-line treatment, four patients failing dolutegravir had confirmed major drug resistance mutations versus none failing darunavir/r.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical and virological characteristics of each single subject should be considered before choosing drugs either for ART-naïve or -experienced PLWH. In particular, late presentation, tolerability to previous drugs, patient's lifestyle , drug-drug interactions, viral subtype, history of previous virological failures or transmitted resistance and even residual viremia can play a role in the maintenance of the long-term efficacy of ART [15,16]. In addition, definitive data on the long-term success of the newest therapeutic strategies are still lacking due to their recent introduction in clinical practice, and the best way to study them throughout time, is still object of debate and research.…”
Section: Introductionmentioning
confidence: 99%